Comparative clinical competence of two commercial injectable ivermectin against caprine haemonchosis (Haemonchus contortus) - Akanda, Md; Islam, Md; Hossain, Md; Al Masud, Abdullah (International Journal of Biological Research, 2014)
The foremost purpose of the study reported here was to perform a pharmacological evaluation of two different injectable ivermectin formulations in goats infected with haemonchosis. Twenty one (n=21) goats were randomly divided into three groups A, B and C whereas each group consisted of seven (n=7) goats. Product A and Product B were injected subcutaneously to the goat in group A and group B, respectively. Goat in group C was kept as infected control group giving any treatment. With 7th, 14th, 21th and 28th days of treatment, a significantly (P<0.01) decreased of egg per gram (EPG) count was found in treated goat of group A and B, respectively. In experimental period, the EPG count of control group C were significantly (P<0.01) increased. In group A and B reduction of mean EPG on 7th, 14th, 21th and 28th day after treatment were 83.9%-80.8%, 81.7%-80.7, 78.1%-77.0% and 73.7%-61.2%, respectively, whereas in control group C the mean EPG were 6.7%, 9.2%, 21.4% and 30.9%, respectively. The body weight was increased significantly (P<0.01) after treatments in group A and B, respectively except untreated control group C. To sum up, two commercial products contain ivermectin have similar clinical competence against haemonchosis in goat. Keywords: Clinical Competence, Goat, Ivermectin, Haemonchosis.